Deteksi Kapal Penangkapan Ikan Menggunakan data Visible Infrared Imaging Radiometer Suite (VIIRS) dan data Vessel Monitoring System (VMS) di Wilayah Pengelolaan Perikanan Negara Republik Indonesia - Awak, Dominggus Samuel Helberth Lothar Matheus Koreri; Lumban-Gaol, Jonson; Kushardono, Dony (Journal of Marine and Aquatic Sciences; Vol 8 No 1 (2022), 2022)
The small pelagic fisheries are one of the most important fish resources for the Indonesian economy. One of the problems for the fisheries industry in Indonesia's is overfishing, along with advances in fishing technology that result in catching activities that exceed sustainable fishing rates and are not offset by good management. This research aims to analyze the integrated distribution of fishing vessels from VIIRS vessel detection data and VMS data in Indonesia's fisheries management areas. To support management efforts, studies on the distribution of vessels that are operating in Indonesian waters need to be known definitively. Currently, the monitoring of the distribution of fishing vessels in the Indonesian area is carried out using a vessel monitoring system. Apart from VMS, detection of fishing vessels can be done by utilizing remote sensing data from both active and passive sensors, namely through the Suomi National Polar-orbiting Partnership satellite which has a visible infrared imaging radiometer suite. This instrument has a day/night band capable of recording lights on the earth's surface, including fishing boats that use the light as a fishing aid. The fishing vessel detection method uses a combination of VBD data from VIIRS satellite imagery and fishing vessel VMS data. Based on the result, VMS matching with VBD is 26.04%, and based on the combination of VIIRS and VMS data, it is known that the area with the most ship distribution is in WPP-712